Nickel-titanium coil springs and repelling magnets: a comparison of two different intra-oral molar distalization techniques. - (:unkn) unknown (My University, 1997)
The aim of this study was to compare two intra-oral molar distalization procedures, involving 15 cases with Class II molar relationships. Magnetic devices were applied to the upper right first molars in each case, while nickel-titanium coil springs were used against the upper left first molars, for a period of 3 months. Measurements were made from lateral cephalograms and from photocopies of models taken before and after the distalization procedure. Although upper molar distalization was achieved with ease in both techniques, nickel-titanium coil springs were found to be the more effective in terms of movement achieved.